ROBOTIKA DALAM MANUFAKTUR: KECERDASAN BUATAN MENGANTARKAN OTOMATISASI DAN KOLABORASI MANUSIA-ROBOT KE TINGKAT YANG NYATA - Muhammad Subhan Abdullah; Rizko Ramdhan Priatna; Muhammad Irfan Maulana; Maulana Yusuf; Perani Rosyani (Buletin Ilmiah Ilmu Komputer dan Multimedia, 2023)
The use of collaborative robots (cobots) in the manufacturing industry aims to enhance productivity, address the shortage of skilled labor, and improve job satisfaction. The "Collaborative APAC-Cobot Expo 2021" event, organized by Universal Robots, serves as a response to the challenges faced by businesses regarding an aging workforce and labor shortages. The cobot market is projected to continue growing worldwide, including in the Asia Pacific region and Indonesia. The adoption of robotic technology provides significant benefits to the Indonesian industry, particularly in realizing the vision of Industry 4.0. A case study on the implementation of cobots in Yokota Corporation is also presented as an example of successful cobot integration, leading to increased production without requiring additional human resources. Collaborative automation, as a future business strategy post-Covid-19 pandemic, combines the strengths of humans and robots, leading to improved job satisfaction and career advancement. Universal Robots addresses supply chain challenges and labor shortages in the industry through the implementation of collaborative automation. Successful implementation of collaborative automation has been observed in the Asia Pacific region, and this article highlights the opportunities offered by this automation trend. The development of collaborative robots (cobots) as an alternative automation solution within the context of Industry 4.0 in Indonesia is crucial. The Indonesian government's "Making Indonesia 4.0" roadmap recognizes automation as a significant step towards Industry 4.0. Cobots are considered a necessary technology for the development of Industry 4.0 in Indonesia. The advancement of robotic automation in the manufacturing industry in Indonesia is essential for maintaining competitiveness and efficiency in challenging economic conditions. This article highlights Universal Robots, a leading collaborative robot technology company, offering cobots to enhance productivity in the manufacturing sector. The potential benefits of utilizing cobots in improving efficiency and productivity in the manufacturing industry are also discussed.